Role of Nevoid Basal Cell Carcinoma Syndrome (NBCCS) in Malignant Transformation of Odontogenic Keratocyst (OKC) - Istiati; Almaratush Sholihah Putri Sisandi (Dentika: Dental Journal, 2026)
dontogenic Keratocyst (OKC) is a cyst lesion characterized by potential for malignant transformation, high recurrence potential, and occurrence as multiple lesions. Malignant transformation is mainly associated with Nevoid Basal Cell Carcinoma Syndrome (NBCCS), also known as Gorlin-Goltz syndrome, a genetic disorder caused by mutations in the PTCH1 tumor suppressor gene (TSGs). PTCH1 mutation may contribute to alterations in certain TSGs, such as p16 and p53, leading to dysregulation of cell cycle control, especially in the G1-S phase. These alterations impair DNA repair mechanisms, promote abnormal apoptotic processes, and facilitate malignant progression, thereby contributing to the aggressive behavior of OKC. Therefore, this study aimed to determine the role of NBCCS in the malignant transformation of OKC. Keywords: OKC, NBCCS, PTCH1 gene, cell cycle